Fingertips Ischemia, Nephroangiosclerosis, and Focal Segmental Glomerulosclerosis: Is Genetic Thrombophilia the Unique Explanation? - Lisa Giovannini; Carlo Donadio (Case Reports in Medicine)
Case Presentation. 53-years-old-man with essential hypertension and nonnephrotic proteinuria (1.3 gr/24 h) and with normal renal function (eGFR-MDRD 123 mL/min/1.73 m2) was admitted to nephrology department; kidney biopsy showed FSGS; two years later the patient presented with ulceration and ischemic gangrene of the IV and V right-hand fingertips; genetic analysis demonstrated polymorphism of the methylenetetrahydrofolate reductase genes C677T (heterozygote C677T/1298AC with normal value of homocysteine) and mutations of prothrombin gene G20210A and of plasminogen activator inhibitor-1 4G/5G 675 with slight increase of its value. After five years from biopsy, 24-hours proteinuria was still around 1–1.3 g/die; renal function was still normal (eGFR 107 ml/min/1.73 m2). These data are against the previous diagnosis of primary FSGS. We hypothesize that genetic thrombophilia may explain all the clinical signs of our patient. Conclusions. Alterations in genes of thrombophilia should be ruled out in patients with bioptic diagnosis of “primary” FSGS, in particular if clinically atypical.